PREVALENCE OF TOXOPLASMA GONDII ANTIBODIES IN HUMAN BEINGS AND COMMENSAL RODENTS TRAPPED FROM LAHORE, PAKISTAN. - M. S. Ahmad; A. Maqbool; M. Mahmood-ul-Hassan; M. Mushtaq-ul-Hassan; A. A. Anjum (Journal of Animal and Plant Sciences, 2012)
An endeavor was made to assess the prevalence of Toxoplasma infection in humans and in rodents captured from the corresponding areas of Lahore using the Latex Agglutination Test (LAT). Sera samples of Rattus rattus (n=210), Mus muscular (n=90) and human beings (n=300) were screened for antibodies against T. gondii. Highest percentage of positive cases (58.57%) was recorded in R.rattus followed by M.muscularus (36.66%) and lowest in human beings (11.33%). Sera samples from human beings showed significant difference in relation to positive level of antibodies against T. gondii at different age groups. Highest percent prevalence of antibodies (28%) was observed in human sera samples collected from more than 51 years of age group followed by 41-50 years age group (17.33%). Remaining two age groups (21-30 and 31-40 years) were negative for anti-T. gondii antibodies. Anti-T. gondii antibodies were detected in sera of rodents and human beings residential of same localities. So, rodents can play role in the transmission of T. gondii to human beings.
Keywords: NA